Output Feedback Stabilization for a Class of Cascade Nonlinear ODE-PDE Systems - Chang, Yanjie; Sun, Tongjun; Zhang, Xianfu; Chen, Xiandong (International journal of control, automation, and systems, 2021)
In this paper, the output feedback stabilization problem is studied for a class of cascade nonlinear ODE-PDE systems. The nonlinear terms of ODE-subsystem are assumed to be bounded by a known constant multiplied by unmeasured states, and PDE-subsystem is a diffusion equation. Especially, the unstable diffusion equation is considered. Based on the low gain observer and a series of transformations, the output feedback stabilization problem is converted into designing proper gain parameters. Furthermore, the stability of the closed-loop system is analyzed by Lyapunov theorem. Finally, two numerical examples are given to demonstrate the effectiveness of the proposed control strategy.